Coerência sintática do sistema trimodal em duas obras de José Siqueira - Silva, Aynara Dilma Vieira da (2013)
This dissertation examines the syntactic coherence of the Trimodal system of José Siqueira, through the analysis of the Quarta Sonatina for piano (1963) and Três Estudos para Flauta e Piano (1964) in light of three methodological procedures. The first of these procedures is the quantitative hierarchization of the harmonic structures, resulting in a new type of classification of the vertical entities, while proposing a method for identification and classification of the syntax of voice-leading between these structures; the second procedure is based on the concept of parsimonious connection from the Neo-Riemannian Theory and aims at investigating how the harmonic structures are connected to each other; and the third evaluates the impact of the relationship of pertinence and encapsulation between the pitchclass set in the syntactic connections between the sonorities. The application of these methodological procedures allow us to characterize a syntatic profile for the three analyzed works, revealing fundamental aspects regarding the consistency of the Trimodal system. It is still our intention that this work, which here gives a highly analytical look on a small portion of the work of Siqueira, would serve as a reference for research so that one can carry out the examination of other works of this composer, as well as other Brazilian composers who worked on the threshold between tonality and atonality, and that it would also extend its boundaries of applicability through the dialogue with other fields of research in music, especially that of musical composition, which will benefit from the modeling implemented here from a prescriptive approach.